Production Constraints and Improvement Strategies of Cowpea (Vigna unguiculata L. Walp.) Genotypes for Drought Tolerance - Gabriel V. Nkomo; Moosa M. Sedibe; Maletsema A. Mofokeng (International Journal of Agronomy)
Cowpea (Vigna unguiculata L. Walp. L) is an important leguminous crop largely grown by smallholder farmers in sub-Saharan Africa for food security and animal feed. The objective of this study was to review the production constraints and improvement strategies of cowpea genotypes for drought tolerance. Data were analysed through use of literature review from various sources. In sub-Saharan Africa, cowpeas are produced mainly from West Africa, which accounts for 60% of worldwide production. A lot of pests and diseases affect cowpeas, and this often results in total crop loss. Through continuous improvement, many new cultivars are continually being identified and genetically characterised, and it is thus necessary to evaluate these new lines under different environments. There is a need for multidisciplinary collaborations among breeders and other relevant stakeholders such as farmer and extension workers because the improved cultivars must be according to the farmers preferred traits. Due to declining rainfall pattern in sub-Saharan Africa, there is an urgent requirement for cowpea breeding programmes that focus on developing varieties with short maturity, drought, pest, and disease tolerance. The present review discusses the constraints and improvement strategies of cowpea varieties for drought tolerance.